Using the electrokinetic remediation (EKR) technique for the soil remediation from the contaminants. Issue 1 (2nd January 2023) - Biabanaki, Faraz; Neshati, Jaber; Ehteshami, Majid
ABSTRACT: Nowadays, soil pollution caused by petroleum extraction has received much attention due to its negative environmental impact. Hence, the present study aims to propose the optimal solution to confront the environmental damage of contaminated soil. The major novelty of this work lies in the accuracy of the electrokinetic technique used in the study. The electrokinetic remediation (EKR) technique is considered for soil remediation, and seven tests are conducted, among which only four tests present efficient results. Notably, Kaolinite is the soil considered in this study, and the soil is contaminated with diesel fuel. The experiments are performed in 3 and 10 days with 20 and 30 V. The initial pollutant contents are 10% and 20%, based on which the results are analyzed. The obtained results represent the remarkable capability of the EKR method for soil remediation and highlight the most optimal condition for each test. The contributions of this study are considered beneficial for those environmental managers aiming to tackle soil pollution with the best approach.